Investigating the design of macromolecular-based inks for two-photon 3D laser printing - Catt, Samantha; Vázquez-Martel, Clara; Blasco, Eva (Molecular systems design & engineering, 2024)
Two-photon 3D laser printing (2PLP) is one of the most versatile methods for additive manufacturing of micro- to nano-scale objects with arbitrary geometries and fine features. With advancing technological capability and accessibility, the demand for new and versatile inks is increasing, with a trend toward printing functional or responsive structures. One approach for ink design is the use of a macromolecular ink consisting of a ‘pre-polymer’ functionalized with photocrosslinkable groups to enable printability. However, so far the synthesis of pre-polymer inks for 2PLP often relies on an arbitrary choice rather than systematic design. Additionally, current structure-property relationship studies are limited to commercial or small molecule-based inks. Herein, three macromolecular inks with varied compositions, molecular weights, and glass transition temperatures are synthesized and formulated into inks for 2PLP. 3D microstructures are fabricated and characterized in-depth with scanning electron microscopy as well as infrared spectroscopy and nanoindentation to enable the determination of structure-processability-property relationships. Overall, it is clearly demonstrated that the macromolecular design plays a role in the printability and mechanical properties of the obtained materials.
Gesehen am 13.01.2025